Incremental and twice weekly haemodialysis in Australia and New Zealand. Issue 11 (1st May 2019) - Wolley, Martin J; Hawley, Carmel M; Johnson, David W; Marshall, Mark R; Roberts, Matthew A
ABSTRACT: Background: Haemodialysis is usually started at a frequency of three times a week, with occasional patients starting twice weekly ('incremental dialysis'). Incremental haemodialysis (HD) may preserve residual kidney function and has been associated with reduced mortality. In the present study, we report prevalence and outcomes of incremental dialysis in Australia and New Zealand. Methods: The cohort was all adults starting renal replacement therapy with HD in Australia and New Zealand 2004–2015. We used cox proportional hazards modelling with a primary exposure of dialysis frequency at first survey date (≥ or <3 times per week). The primary outcome was all‐cause mortality (primary), cardiovascular and non‐cardiovascular mortality (secondary). Results: Eight‐hundred fifty of 27 513 subjects were started on twice weekly HD (prevalence 3%). Compared to conventional patients, incremental dialysis patients were older (67 vs 62 years, P < 0.001), had a lower body mass index (26.1 vs 27.7 kg/m 2, P < 0.001), had a higher starting estimated glomerular filtration rate (7.59 vs 6.66 mL/min P < 0.001) and had less diabetes (39.2% vs 50.2%, P < 0.001). In a multivariate model, incremental start dialysis was not associated with all‐cause mortality (hazard ratio (HR) = 1.03, 95% confidence interval (CI) = 0.92–1.16) or cardiovascular mortality (HR = 0.87, 95% CI = 0.71–1.07), but was associated with an increased risk of non‐cardiovascular mortality (HR = 1.25, 95% CI = 1.11–1.42). Conclusion: Incremental dialysis was used infrequently, and there was evidence of patient level differences. All‐cause mortality was similar, but there were differences in cause specific mortality. Incremental dialysis needs to be tested in prospective trials to define the safety and efficacy of this approach. SUMMARY AT A GLANCE: This study analyzed a cohort of incident dialysis patients from the Australian and New Zealand Dialysis and Transplant registry to define the prevalence of use of incremental dialysis, the factors associated with patients undergoing incremental dialysis and whether incremental dialysis was associated with lower mortality. The conclusion of this study was that all‐cause mortality was similar between conventional and incremental dialysis. Incremental dialysis needs to be tested in prospective trials to define safety and efficacy.